Driven by the Markets? ECB Sovereign Bond Purchases and the Securities Markets Programme - Ansgar Belke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
After the dramatic rescue package for the euro area, the governing council of the European Central Bank decided to purchase European government bonds - to ensure an 'orderly monetary policy transmission mechanism'. Many observers argued that, by bond purchases, national fiscal policies could from now on dominate the common monetary policy. This note argues that they are quite right. The ECB has indeed become more dependent in political and financial terms. The ECB has decided to sterilise its bond purchases - compensating those purchases through sales of other bonds or money market instruments to keep the overall money supply unaffected. This is to counter accusations that the ECB is monetizing government debt. This note addresses how effective these sterilisation policies are. – – Nach dem riesigen Hilfspaket für den Euroraum hat der Rat der Europäischen Zentralbank (EZB) beschlossen, Staatsanleihen europäischer Länder anzukaufen - um einen 'geregelten geldpolitischen Transmissionsmechanismus' zu garantieren. Viele Analysten äußern Bedenken, dass durch die Anleihenkäufe von nun an die Geldpolitik von den nationalen Fiskalpolitiken dominiert wird. In diesem Beitrag wird argumentiert, dass die Kritiker richtig liegen. Die EZB ist tatsächlich unter politischen und finanziellen Aspekten abhängiger geworden. Die EZB hat beschlossen, ihre Anleihenkäufe zu sterilisieren - diese Geschäfte werden durch Verkäufe anderer Anleihen oder Geldmarktinstrumente kompensiert, um das Gesamtgeldangebot konstant zu halten. Damit soll den Anschuldigungen entgegen getreten werden, die EZB monetisiere Staatsschulden. In diesem Beitrag wird untersucht, wie effektiv diese Sterilisationspolitiken sind.
Keywords: G32; E42; E51; E58; E63; 330; accountability; bail-out; bond purchases; central bank independence; insolvency risk; Securities Markets Programme; transparency